How Gamma Waves and Motor Educability Correlate to Movement Performance in Gymnastics - Vanya Raissya; Jajat Darajat Kusumah Negara; Helmy Firmansyah; Yunyun Yudiana; Rion Hendrianto (Universitas Pendidikan Indonesia, 2023)
This study was aimed to determine how gamma waves and motor educability correlate to gymnastics movement performance of West Java gymnastic athletes. The study used quantitative descriptive method with a correlational design. The population and sample of this study were 13 West Java gymnastic youth athletes selected using saturated sampling technique. The instruments used were gymnastic performance tests, motor educability test (IOWA Brace test), and brain wave test using the Emotiv EPOC Wireless helmet. Based on data processing and analysis, the correlation value between gamma brain waves and movement performance was r= -0.620 with a p -value 0.024 0.05, while the coefficient of determination was 0.384, meaning that there was a contribution of 38.4%. It concludes that, there was a negative functional correlation between gamma brain waves and movement performance. The obtained correlational value between motor educability and gymnastic performance was r = 0.646 with a p-value 0.017 0.05 and a coefficient of determination of 0.418, showing that there was a contribution of 41.8%. It implies that that there was a positive functional correlation between motor educability and gymnastic performance. The correlation value of gymnastic performance, gamma brain waves, and motor educability was r = 0.749 with a p-value 0.016 0.05 and coefficient of determination of 0.560, indicating that gymnastic performance was determined by gamma brain waves and motor educability of 56.0%. The results showed that there was a strong correlation and a significant contribution of gamma waves and motor educability to movement performance in gymnastics.